Anemia Prevention Therapy in Pregnant Women - Yusuf, Nuuva; Anggraini, Ryzky Diah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2022)
Anaemia is a problem that often occurs in pregnant women, which, if not above, can result in impaired fetal growth and even death. Green beans are a source of food that contains iron, vitamin C and zinc. This research aims to analyze the effect of giving green beans toward the increase of haemoglobin level on pregnant women with anaemia in the working area of Puskesmas. The research method is the kind of pre-experimental research using the approach of one group pretest-posttest design. The sample is 30 pregnant women with anaemia. The sampling technique uses purposive sampling. Haemoglobin level was carried out before and after the experiment, and green bean porridge was given to the respondents 2 times a day for 7 days. The results showed that the level of pregnant women's haemoglobin treated increases averagely as much as 1.17g/dL. The result of data analysis using paired T-test obtains p-value = 0,000<α 0.05. There is a significant effect of giving green beans to increase haemoglobin levels on pregnant women with anaemia. It is hoped that midwives can provide counselling about the benefits of giving green bean porridge to increase haemoglobin levels in pregnant women with anaemia.